The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0102-05362009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa de capacidades de combinação em gerações iniciais de seleção de batata

Abstract: Verificou-se as estimativas das capacidades de combinação de genitores de batata em gerações iniciais de seleção. Os experimentos foram realizados na Embrapa Clima Temperado, Pelotas (RS). Foram avaliadas 20 famílias derivadas de nove genitores cruzados em esquema parcial 4 x 5 (C-1750-15-95; 2CRI-1149-1-78; C-1786-6-96 e 'Eliza'; 'White Lady'; 'Asterix'; 'BP-1'; 'Vivaldi' e 'Ágria'). As famílias foram avaliadas na geração de plântula e na primeira geração de campo, utilizando o delineamento experimental de bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(2 reference statements)
2
0
0
4
Order By: Relevance
“…The predominance of SCA for tuber number and a higher GCA for average tuber weight were reported by Tai and De Jong (1991), who concluded that tuber number results from continuous directional selection, while the average tuber weight results from stabilization in selection. A similar significance of SCA and GCA for tuber yield traits was also observed by Silva et al (2009).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The predominance of SCA for tuber number and a higher GCA for average tuber weight were reported by Tai and De Jong (1991), who concluded that tuber number results from continuous directional selection, while the average tuber weight results from stabilization in selection. A similar significance of SCA and GCA for tuber yield traits was also observed by Silva et al (2009).…”
Section: Resultssupporting
confidence: 78%
“…For parents of group 2, 'Eliza' stood out with more positive values for tuber appearance traits. For the set of tuber yield component traits, 'Rioja' of group 1 performed best, since the GCA values were highest, similar to those reported by Silva et al (2009). For the trait skin texture, the most stable results of all four evaluations, the cross 'Caesar'/'C1730-7-94' showed the highest positive values, contributing to a smoother skin.…”
Section: Resultssupporting
confidence: 77%
“…Diferentemente do relatado por Silva et al (2009), em estudo com outras combinações, o genitor 'Eliza' não apresentou valor elevado de CGC para número de tubér-culos. No grupo 2, 'White Lady' foi o genitor com os maiores valores de CGC para número de tubérculos, na geração de plântula e na primeira geração de campo.…”
Section: Genitorunclassified
“…Por outro lado, 'Asterix' teve os maiores valores negativos nos dois locais, contribuindo com efeitos negativos de CGC para massa média de tubérculos, ou seja, favorecendo tubérculos com pequena massa média. Os resultados indicam que 'White Lady' contribui com genes aditivos para esse caráter, enquanto 'Asterix' apresenta efeito contrário, confirmando os resultados de Silva et al (2009).…”
Section: Genitorunclassified
See 1 more Smart Citation